Airport retailing at Mondelez: The launch of Toblerone crunchy almond in Asia - RAMASWAMI, Seshan (Institutional Knowledge at Singapore Management University, 2019)
The case describes the challenges and opportunities of airport retailing in the confectionery category from both manufacturers’ and retailers’ perspectives. It is based in 2012, when Mondelez planned to launch a new flavour of its flagship brand, Toblerone, the first in 15 years, at Singapore, Bangkok and Kuala Lumpur international airports. The airport retail market was significant for Mondelez, and in particular, for the Toblerone brand, given that 23% of its sales came from the airport retail market. Distinctive consumer and shopping behaviour at airport confectionery stores, market segmentation by type of passenger and purchase motivation, importance of promotions, personal selling, display and sampling, and regional differences in the three airport markets were the key considerations for Mondelez while planning the launch of the new variant. Moreover, the timing of the proposed launch coincided with the upcoming festival season, a peak time for confectionary retailers at airports. The main takeaway from the case is a detailed understanding of how multiple factors influence airport retailing of confectionary brands and how it is significantly different from supermarket or city-side retailing. The case can be used for courses in Introductory marketing (Retailing and Consumer Behaviour sessions to introduce shopper behaviour characteristics), and Brand Management (launch of a new flavour of a leading brand). The case could also be used in a course on Retailing Management, to illuminate the unique challenges of airport retailing, and the dynamics of the manufacturer-retailer relationship. A set of slides that can be used to teach the case have been included in the Appendix.